Is microscopic examination of hysterectomy specimens removed for clinically benign disease necessary?. Issue 2 (3rd August 2007) - Andrews, T; Monaghan, H
Abstract : The likelihood of finding significant pathology in a hysterectomy specimen undertaken for clinically benign disease is low. Some data indicate that microscopic examination of these specimens may be abandoned. While this approach may seem attractive, the authors believe that there are a number of practical and clinical governance issues associated with this. Instead a pragmatic approach is advocated, with two tissue blocks (cervix and endomyometrium) being adequate in most cases.